Orexin, cardio-respiratory function, and hypertension - Li, Aihua; Nattie, Eugene E. (Frontiers in Neuroscience, 2014)
In this review we focus on the role of orexin in cardio-respiratory functions and its potential link to hypertension. 1) Orexin, cardiovascular function and hypertension. In normal rats, central administration of orexin can induce significant increases in arterial blood pressure (ABP) and sympathetic nerve activity (SNA), which can be blocked by orexin receptor antagonists. In spontaneously hypertensive rats (SHRs), antagonizing orexin receptors can significantly lower blood pressure under anesthetized or conscious conditions. 2) Orexin, respiratory function and central chemoreception. The prepro-orexin knockout mouse has a significantly attenuated ventilatory CO2 chemoreflex, and in normal rats, central application of orexin stimulates breathing while blocking orexin receptors decreases the ventilatory CO2 chemoreflex. Interestingly, SHRs have a significantly increased ventilatory CO2 chemoreflex relative to normotensive WKY rats and blocking both orexin receptors can normalize this exaggerated response. 3) Orexin, central chemoreception and hypertension. SHRs have higher ABP and SNA along with an enhanced ventilatory CO2 chemoreflex. Treating SHRs by blocking both orexin receptors with oral administration of an antagonist, almorexant (Almxt) can normalize the CO2 chemoreflex and significantly lower ABP and SNA. We interpret these results to suggest that the orexin system participates in the pathogenesis and maintenance of high blood pressure in SHRs, and the central chemoreflex may be a causal link to the increased SNA and ABP in SHRs. Modulation of the orexin system could be a potential target in treating some forms of hypertension.